The Design of Tropical Homes in Focus of Climate Conditions - Penner, Jonas (Journal of A Sustainable Global South; Vol 8 No 1 (2024): February 2024DO - 10.24843/jsgs.2024.v08.i01.p06, 2024)
The topic I would like to address in this paper is about the design of tropical homes with a specific focus on climate conditions, construction, and design elements. In fact, tropical areas deal with different circumstances such as heat, humidity and heavy rainfall. All these extreme challenges can occur at the same time. For this reason, it requires to plan these houses carefully to get the perfect protection for any weather extreme. In order to counteract the problems, there are several solutions you can perceive during the planning phase. One key proposed solution involves strategic placement on the property. Orienting the longer sides of the house toward the north and south minimizes direct sunlight exposure. This helps to maximize natural ventilation and reduce heat gain inside the house. Another critical factor contributing to effective ventilation is cross-ventilation, achieved by situating windows and doors on opposing sides of the house. This arrangement facilitates the flow of air, reducing internal temperatures. Another aspect of the ventilation is the roof structure. Having openings in the roofs, helps to release hot air which accumulate in the top of the building. A further aspect you can do with the roof is to plan a roof overhang so that it protects walls from heavy rainfall and protects openings from sunlight. By integrating these design principles, you can create a house that is comfortable, resilient, and well-suited to the unique conditions of tropical regions.